Carotenoids (IntechOpen, 2023)
Carotenoids are one of the most widespread pigment groups distributed in nature; more than 700 natural carotenoids have been described so far. These pigments are known for versatile roles they play in living organisms; however, their most pivotal function is involvement in scavenging of reactive oxygen species and photoprotection. In the same time, carotenoids as natural pigments with important biological activities, such as antioxidant and provitamin A activity, have a great potential in the food, feed and pharmaceutical industries. They can be either extracted from plants and algae or synthesized by various microorganisms, including bacteria, yeasts, filamentous fungi and microalgae.